2017
DOI: 10.1159/000480367
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Inhibition Contributes to ROS-Producing NLRP3-Dependent Inflammasome Activation and Cytokine Secretion in High Glucose-Induced Macrophages

Abstract: Background: Type 2 diabetes is a persistent inflammatory response that impairs the healing process. We hypothesized that stimulation with high glucose following a pro-inflammatory signal would lead to autophagy inhibition, reactive oxygen species (ROS) production and eventually to the activation of the Nod-like receptor protein (NLRP) -3. Methods: Macrophages were isolated from human diabetic wound. We measured the expression of NLRP3, caspase1 and interleukin-1 beta (IL-1β) by western blot and real-time PCR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 27 publications
3
53
0
1
Order By: Relevance
“…It is worth noting that enhancing autophagy induced the activation of NLRP3 inflammasome in Caco-2 cells. In contrast, it was reported that inducing autophagy suppressed the activation of NLRP3 inflammasome in rat [47], and that autophagy inhibition contributed to NLRP3 inflammasome activation in macrophages [49]. Therefore, the exact relationship between autophagy and NLRP3 inflammasome is still a complex and controversial issue to be clarified.…”
Section: Discussionmentioning
confidence: 95%
“…It is worth noting that enhancing autophagy induced the activation of NLRP3 inflammasome in Caco-2 cells. In contrast, it was reported that inducing autophagy suppressed the activation of NLRP3 inflammasome in rat [47], and that autophagy inhibition contributed to NLRP3 inflammasome activation in macrophages [49]. Therefore, the exact relationship between autophagy and NLRP3 inflammasome is still a complex and controversial issue to be clarified.…”
Section: Discussionmentioning
confidence: 95%
“…Several papers reported on the possible negative role of GM1 in the formation of neurotoxic β-amyloid fibrils at the cell surface [141][142][143][144][145]. A claim was made that GM1 would act favoring the deposition of the aggregates following specific interaction requiring the GM1 high clustering [146][147][148].…”
Section: Gm1 and Alzheimer's Diseasementioning
confidence: 99%
“…Additionally, the inflammation induced by CIRI is significantly enhanced in patients with diabetes [8]. An in vitro study also found that high glucose induces ROS production and activates cytokine secretion [9]. The expression of calcium sensing receptor in hippocampal neurons also decreased after treatment with high glucose and then increases the production of ROS in mitochondria [10].…”
Section: Introductionmentioning
confidence: 97%